2008
DOI: 10.1177/102986490801200105
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between expressed and felt emotions in music

Abstract: This study examines empirically the possible relationships between the emotional quality one can attribute to musical stimuli (expressed emotion, or external locus of emotion) and the subjective emotional response one can have as a result of listening to music (felt emotion, or internal locus). The relationship between the two loci of emotion is often assumed to be positive, that is, when listening to music, one feels the emotion that the music expresses. Gabrielsson has suggested, however, that this assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
123
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 41 publications
7
123
0
6
Order By: Relevance
“…perceived emotions), but whether or not it induces those emotions in a listener (induced emotions) is another matter. Sometimes the emotion induced is the same as that perceived, as these two processes bear some resemblance to each other (Evans & Schubert, 2008;Vieillard et al, 2008), but this is not always the case. In terms of computational modelling, the emotions perceived in music provide a better object of modelling, since they rely more on the musical features than an individual's felt experiences (induced emotions), which are prone to subjective associations and contextual effects (Gabrielsson, 2002;Juslin & Va¨stfja¨ll, 2008).…”
Section: Emotions and Musicmentioning
confidence: 99%
“…perceived emotions), but whether or not it induces those emotions in a listener (induced emotions) is another matter. Sometimes the emotion induced is the same as that perceived, as these two processes bear some resemblance to each other (Evans & Schubert, 2008;Vieillard et al, 2008), but this is not always the case. In terms of computational modelling, the emotions perceived in music provide a better object of modelling, since they rely more on the musical features than an individual's felt experiences (induced emotions), which are prone to subjective associations and contextual effects (Gabrielsson, 2002;Juslin & Va¨stfja¨ll, 2008).…”
Section: Emotions and Musicmentioning
confidence: 99%
“…The internal assessment, however, can result in an emotional experience that is evoked in the observer himself or herself by the percept (e.g., "I feel sad, angry"). The separation of these perspectives is essential as the perception of emotional qualities is not necessarily accompanied by a consciously perceived or objectively assessable emotional change or (physiological) reaction in the observer (Evans & Schubert, 2008;Gabrielsson, 2002;Kallinen & Ravaja, 2006;Russell & Snodgrass, 1987). Although it was found that for instance music-induced experienced emotions and perceived emotions in response to happy and sad music are highly correlated, it is not clear whether this also holds for emotions induced by stimuli originating from other sensory domains (Konecni, 2008;Scherer, 2004;Zentner, Grandjean, & Scherer, 2008).…”
Section: Higher Order Processes: Perception and Emotionmentioning
confidence: 99%
“…The actual experiences induced by music expressing sadness, however, may not 70 always be aligned with the expressed emotional content [21]. These deviations are explained by distinct emotion induction mechanisms and construction of meaning, explained in the third premise.…”
mentioning
confidence: 99%